Exploring How Evidence-Based Practice, Communication, and Clinical Simulation Outcomes Interact in Nursing Education: A Cross-Sectional Study - José Jorge Carrasco-Guirao; César Leal-Costa; María de los Ángeles Castaño-Molina; Maria Belén Conesa-Ferrer; Alonso Molina-Rodríguez; José Luis Díaz-Agea; Maria Gracia Adánez-Martínez (MDPI AG, 2024)
(1) Background: Clinical simulation is an educational approach that aims to replicate real-life scenarios. Its primary goal is to help nursing students acquire the necessary knowledge and skills to perform effectively in clinical settings. This study focuses on the relationship between communication skills, evidence-based practice (EBP), and clinical simulation. We aimed to assess how communication skills and EBP competencies affect nursing students' performance in simulated clinical scenarios. (2) Methods: We conducted an observational, cross-sectional study with 180 third-year nursing students at the University of Murcia. We used validated instruments to evaluate the students' EBP competencies, communication skills, non-technical skills, and nursing interventions in simulated scenarios. (3) Results: The results showed that the students had varying competencies in EBP and communication skills. However, there was a positive and statistically significant correlation (p < 0.001) between these variables, non-technical skills, and the simulated clinical scenario nursing interventions. Our regression models revealed that communication skills and EBP competence significantly influenced the performance of the student nurses regarding their clinical and non-technical skills in the simulated scenarios. (4) Conclusions: Communication skills and EBP competencies predict performance in simulated scenarios for nursing students.